A novel virtual inductor optimization methodology of virtual synchronous generators for enhanced power decoupling - Xin Zhang; Lijiao Gong; Yanjun Zhang; Xiaolei Ma; Lianshan Han; Santao Jiang; Weiji Zhou (International Journal of Electrical Power & Energy Systems)
The integration of increasing amounts of inverter-interfaced generation units into power network presents critical challenges regarding the dynamic behavior and stability of grid-connected power electronic systems. Virtual synchronous generator (VSG) is a promising solution to address these challenges effectively. But the capability of grid-connected inverter power output is limited with resistively-dominated system due to the strong power coupling. This article introduces a novel optimization methodology for virtual inductor within VSG, aimed at enhancing the power decoupling capacity of inverter. Firstly, a dynamic coupling model of VSG incorporating a virtual inductor is established. This model facilitates the analysis of power stability under different control parameters and resistance-to-inductive reactance ratios in the grid line. It enables the preliminary regulation of the system’s steady-state and dynamic characteristics. Secondly, the study formulates the dynamic and static reference voltage equations. Along with the establishment of system’s equivalent impedance model after incorporating virtual inductor. Furthermore, the paper proposes the optimization of virtual inductor’s parameters using a variable function of power coupling degree. This content achieves precise adjustment of the system’s stability, dynamic and decoupling performance. Finally, a series of comparative experiments is conducted to demonstrate its superior dynamic, static performance and enhanced power decoupling characteristics. In addition, a 15 kW inverter laboratory prototype controlled by StarSim rapid control prototyping (RCP) is used to test the proposed methodology. The simulation and experimental results verify the correctness and feasibility of the virtual inductor parameter optimization method.